Glory - Habana, Ino (Likhaan: The Journal of Contemporary Philippine Literature, 2024)
In “Glory,” a young girl’s gaze is trained on her mother, who, in her desire to better their lives, takes on a series of questionable jobs as a secretary to rich men. Vilma is eventually employed by the pastor of a Christian church. She sees this as an opportunity for her daughter to make friends with the wealthy church children, thus giving her connections that might serve her well in the future. However, mother and daughter soon realize that they are not welcome in the church. Vilma loses her job and is forced to leave the church, but she refuses to go without a bang. Glory is a humorous story about religion, socioeconomic class, and the conflicted relationship between a daughter and her mother